Microalgae : Recent micro to macro-applications in South East Asia - Chung, Hung Hui; Leonard Lim, Whye Kit; Qamarul Hafiz, Zainol Abidin; Wan, Wei Wei (Elsevier Ltd., 2025)
Microalgae are unicellular organisms found in aquatic environments, playing a key role in carbon fixation and oxygen production through photosynthesis. They produce valuable bioactive compounds such as proteins, lipids, and antioxidants. Their wide-ranging applications make them a promising sustainable resource. In biofuel production, microalgae serve as an eco-friendly alternative to fossil fuels while aiding in carbon sequestration. In nutraceutical industries, they offer essential nutrients like omega-3 fatty acids and amino acids. The pharmaceutical sectors utilize microalgae-based nanocarriers for efficient drug delivery. Environmentally, microalgae are effective in wastewater treatment and bioremediation due to their pollutant-absorbing abilities. In Southeast Asia, the biomass energy market is expected to grow at 7.6 % compound annual growth rate from 2025 to 2034 and recent studies highlight their growing role in addressing sustainability challenges. As research advances, microalgae continue to emerge as a powerful tool in promoting green technology and solving global environmental and energy issues.